Towards sustainable hydrogen production: A critical review of perovskite photocatalysts and their energy conversion pathways - Ghena Al Batarni (22997764) (2025)
Perovskite materials have emerged as promising catalysts for sustainable hydrogen (H2) production a vital clean energy solution to combat climate change and substitute fossil fuels. Their adjustable crystal structures, remarkable catalytic activity, and advantageous optoelectronic properties facilitate efficient solar-driven water splitting. This review consolidates recent progress in perovskite-based hydrogen production through three main approaches: photocatalytic, thermochemical, and photoelectrochemical (PEC) techniques. Significant advancements include LaTiO2N and Cs2AgBiBr6 combined with reduced graphene oxide (RGO), achieving improved charge separation and hydrogen evolution rates of up to 9.78 μmol. h−1. Composites of methylammonium lead iodide (MAPbI3) with carbonized polymer dots (CPD) achieve solar-to-hydrogen (STH) efficiencies of 2.15 %. In PEC systems, materials such as copper(I) oxide/strontium titanate (Cu2O/SrTiO3) and cadmium sulfide-decorated barium stannate (CdS/BaSnO3) produce photocurrent densities of ≤ 6.9 mA/cm2 and H2 production rates of 12.3 μmol cm−2h−1. Thermochemical cycles utilizing calcium-doped lanthanum manganite-based perovskites (e.g., LCMC8282) achieve rates of 64 μmol·h−1, while lanthanum strontium magnesium manganite (LSMMg) maintains 236 μmol·g−1·h−1 with excellent cyclability. Despite advancements, challenges remain in structural instability, environmental degradation (e.g., lead toxicity), and scalability. Current perovskite systems, while promising in controlled environments, lack the long-term stability and efficiency required for real-world deployment. Bridging the gap between material innovation and operational durability represents the principal barrier to commercialization. We conclude that compositional engineering, lead-free alternatives (e.g., Cs2AgBiBr6), and interface design are crucial for advancing perovskite-based hydrogen technologies toward commercial viability. Other Information Published in: Separation and Purification Technology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.seppur.2025.135035